2019
DOI: 10.1038/s41598-019-42994-1
|View full text |Cite
|
Sign up to set email alerts
|

Neprilysin Inhibitor–Angiotensin II Receptor Blocker Combination Therapy (Sacubitril/valsartan) Suppresses Atherosclerotic Plaque Formation and Inhibits Inflammation in Apolipoprotein E- Deficient Mice

Abstract: We assessed the effects of the sacubitril/valsartan combination drug (LCZ696), in comparison to valsartan alone, on the progression of atherosclerotic plaque formation and inflammatory gene expression in apolipoprotein E- deficient mice (apoE −/− mice). Seventy-two apoE −/− mice were fed a western diet and a constrictive silastic tube was used to elicit carotid lesion formation. The animals were separated into a control group, a valsartan group or an LCZ696 group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 26 publications
(73 reference statements)
0
22
1
2
Order By: Relevance
“…Sacubitril/valsartan reduced the concentration of proinflammatory cytokines and neutrophil count, while increasing lymphocyte count more than valsartan alone or placebo [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sacubitril/valsartan reduced the concentration of proinflammatory cytokines and neutrophil count, while increasing lymphocyte count more than valsartan alone or placebo [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding might be related to the increase in plasma levels of atrial/brain/C-type natriuretic peptide, Ang I/II, substance P, bradykinin and endothelin secondary to neprilisin inhibition by sacubitril. 46 Therefore, administration of an ACE, an ARB or sacubitril/valsartan may even be beneficial through inhibition of AT1R. 47…”
Section: Role Of Cytokine Stormmentioning
confidence: 99%
“…Anti-inflammatory effect mainly driven by the protection of lymphocyte count may be an important feature of sacubitril in patients with chronic heart failure. As an additional clinical effect, early administration of neprilysin inhibitor in decompensated heart failure may also result in a decrease in high sensitive C-reactive protein (hs-CRP) levels (9). In our case, we detected an increase in lymphocyte count and a relative decrease in hs-CRP level at the end of the first week after hospitalization.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies demonstrated an increment in lymphocyte counts in heart failure patients treated by neprilysin inhibitor (9,10). Anti-inflammatory effect mainly driven by the protection of lymphocyte count may be an important feature of sacubitril in patients with chronic heart failure.…”
Section: Discussionmentioning
confidence: 90%